Applicability of inclusive business model for sustainable community based tourism development in Taman Negara Malaysia, Kuala Tahan Pahang, Malaysia - Shuib, Ahmad; Chia, Kei Wei; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman; Nair, Vikneswaran; Ahmad, Nurul Azwa (2012)
The development of rural tourism has been identified as a strategic alternative to overcome the economic decline in the rural agricultural sector. The success of the rural tourism development hinges upon benefits that accrue to the local communities in terms of employment, business opportunities and improved standard of living. The Inclusive Business Model (IBM) is a framework that could expedite and ensure that rural tourism can be sustainable; in the framework the tourism entity plays the role of extending the effects of tourism through employment opportunities, entrepreneurial development, asset accumulation and environmental conservation. The paper explores the existence of IBM criteria in the development of the rural tourism sector at a national park and the applicability of the model in affecting the local community development. The case study shows that in Taman Negara Malaysia, National Park, Kuala Tahan there are elements that could aid in the establishment of IBM, however, there is no championing entity to lead, create and apply the model in the present context.